(In)traduzibilidade das Expressões Idiomáticas entre a Língua Portuguesa e a Língua Brasileira de Sinais: uma análise conceitual e funcional - Scapolan, Bruno Alexandre (2023)
This MA thesis aims to investigate the (un)translatability of Idiomatic Expressions (IEs) between Portuguese Language (PL) and Brazilian Sign Language (Libras) based on a content analysis of four YouTube videos produced by teachers and/or translators/interpreters of Libras and Portuguese Language (TILSP). The research problem revolves around three questions: (1) How do teachers and/or TILSP conceptualize IEs on YouTube videos? (2) How do they define the translational equivalences of IEs between the languages under scrutiny? and (3) Is idiomaticity an aspect also found in the translation of IEs? The research draws on a literature review of the concept of IEs, (un)translatability, and the notions of “formal correspondence” and “textual equivalence” proposed by Catford (1965). The methodology consists of selection and content analysis of YouTube videos and comparison of the findings with the literature in the field. The results sheds light on the definitions of IEs and the notions of their (un)translatability, and also point to the use of different strategies by teachers and/or TILSP to translate IEs, which can affect the levels of idiomaticity (i.e., non-transparency of the expression’s meaning through the individual meanings of its isolate components) in the target language. This MA thesis contributes to deepening and broadening linguistic studies and translation studies on the so-called “formal correspondents” and “textual correspondents”, as well as providing input for a thorough reflection on the teaching/learning and translation of IEs from PL to Libras and vice-versa.